Shared and distinct functions of two Gti1/Pac2 family proteins in growth, morphogenesis and pathogenicity of Magnaporthe oryzae. (30th July 2013) - Chen, Yue; Zhai, Su; Zhang, Haifeng; Zuo, Rongfang; Wang, Jiamei; Guo, Min; Zheng, Xiaobo; Wang, Ping; Zhang, Zhengguang
Summary Gti1/Pac2 are conserved family proteins that regulate morphogenic transition in yeasts such as Schizosaccharomyces pombe and Candida albicans, and they also control toxin production and pathogenicity in filamentous fungus Fusarium graminearum. To test the functions of Gti1/Pac2 paralogues MoGti1 and MoPac2 in the rice blast fungus Magnaporthe oryzae, we generated respective ΔMogti1 and ΔMopac2 mutant strains. We found that MoGti1 and MoPac2 exhibit shared and distinct roles in hyphal growth, conidiation, sexual reproduction, stress responses, surface hydrophobility, invasive hyphal growth and pathogenicity. Consistent with the putative conserved function of MoGti1, we showed that MoGti1‐GFP is localized to the nucleus, whereas MoPac2‐GFP is mainly found in the cytoplasm. In addition, we provided evidence that the nuclear localization of MoGti1 could be subject to regulation by MoPmk1 mitogen‐activated protein kinase. Moreover, we found that the reduced pathogenicity in the ΔMopac2 mutant corresponds with an increased expression of plant defence genes, including PR1a, AOS2, LOX1, PAD4, and CHT1. Taken together, our studies provide a comprehensive analysis of two similar but distinct Gti1/Pac2 family proteins in M. oryzae, which underlines the important yet conserved functions of these family proteins in plant pathogenic fungi.